Análisis socio-jurídico de las infracciones culposas establecidas en el Art. 108 de la ley orgánica de transporte terrestre, tránsito y seguridad vial y su incidencia en la aplicabilidad de los delitos de tránsito ocurridos en la ciudad Santa Rosa en el año 2010. - Villa Chuchuca, Karen Andrea (2011)
This research work has developed around the defense and demonstration of the hypothesis that it is possible the structure of violations of malicious traffic, this is because the development of the criminal dogma has shown several forms of possible fraud, thanks the identification of this category of fraud could show if traffic violations the author achieves a result that although it was not its purpose or necessary, it was a possibility that he had yet accepted it.